Promoting Oral Health in 6-12 Year-Old Students: A Systematic Review - Seyed Mohammad Mehdi Hazavehei; Samane Shirahmadi*; Malihe Taheri; Nesa Noghan; Nafese Rezaei (Hamadan University of Medical Sciences, 2015)
Background and Objectives: The group of 6-12 year-old students are the main target of oral health programs due to the high prevalence of dental caries and the formation of permanent teeth during this age and the lifestyle-shaping nature of the period. Schools provide the easiest and most effective means of accessing this group. The present study was conducted to examine the impact of school-based interventions on improved oral health in 6-12 year-old students. Materials and Methods: The present systematic review searched for its English and Persian keywords in databases such as the Scopus, Proquest, Science Direct, Pubmed, Springer, Biomed Central, Google Scholar, IranMedex and SID and examined studies published between January 2004 and September 2014 about educational interventions aiming to prevent oral diseases and promote associated health behaviors in students. Results: The 17 studies selected for examination were divided into two categories: first, assessing an education based on self-care behaviors and preventive services second, assessing an education based on self-care behaviors only. Those interventions that were consistent in nature, involved the parents and the school personnel, used behavior change models, used a combination of several training methods, used practical experiences and provided preventive services were more effective in promoting knowledge and health behaviors and reducing dental caries and plaque in this group of children. Conclusion: Providing consistent community-based education, using a combination of several organized educational programs, following up on the children's progress, using behavior change theories and models and providing prevention services are the most effective measures for achieving the desired goals.